Meningkatkan Perekonomian Indonesia Melalui Ekspor Obat Herbal Tradisional - Aditama Putra Maulana (Pemuliaan Keadilan, 2024)
Traditional medicine is an ingredient or ingredient in the form of plant material, animal material, mineral material, which has been used for generations for treatment. Herbal medicine is a form of traditional medicine. With the fact that there are many efficacious medicinal plants in Indonesia, tens of thousands of types of medicinal plants can be encouraged to be processed into standardized herbal or herbal medicine (phytopharmaca). This country will be able to become the main exporter of herbal medicinal products for health in the world. This will have a very positive impact on economic growth. Not only in the economic sector, but of course it will further enhance cooperative relations between Indonesia and other countries in the economic sector.